QRmesse: automatização de eventos comunitários - Araújo, Márcio José (2018)
This work presents the development of the QRmesse system, which replaces the sheets used for purchasing products in community events, such as church festivals and school parties. The system implementation required a study, reported here, on the automating process of selling and delivering products, aided by Android mobile devices, as QR Code readers. The application designed for mobile devices integrates to a Java EE system via Web Service. In addition, the QRmesse uses frameworks and libraries that make easier to build the applications Java EE, Web Services, and Android - this work describes their deployment. The system was tested in one event, showing satisfactory performance and usability. From this test, issues came, that were approached and solved. It concludes that the automating of community events provides a better experience to their participants, and so contributes to the success of such events.